Per a la data de l'apitxat - Colón, Germà (Caplletra. Revista Internacional de Filologia, 1999)
This essay's contribution consists of new 15th and 16th century documentary witnesses, ateested by scholars, which show readings with ch spelling instead of other spellings representing the voiced palato-alveolar affricate. The author maintains that these cases, although exceptional in contemporary texts, constitute «crevices in the old edifice of written language» and would confirm the hypothesis that apitxament, the voiceless production of the above-mentioned sound, originated in 15th century Valencia, as opposed to those dating this phenomenon well into the modern period.